A MICROSTRUCTURE ANALYSIS OF HAIDAR AL-ABADI’S DISCOURSE ON THE KURDISTAN REFERENDUM - TAYIB, DILGASH MOHAMMED SALIH; MUHAMMAD, IZZULDDIN RAJAB (Journal of Duhok University, 2023)
Critical discourse analysis is an effective method for analyzing the special relationship between power and the traditional ideology in implied discourse. This paper is aimed at analyzing Haidar Al-Abadi’s discourse on the Kurdistan Referendum at the micro level. It investigates the linguistic elements of Al-Abadi’s discourse at the syntactic and semantic levels based on Van Dijk’s sociocognitive framework. This paper shows how speakers in political speech use language to shorten the distance between people and win people's affirmation and support from the aspects of passivation, pronouns, modality and categorization. At the syntactic level, the speaker uses direct speech to tackle the issue of referendum. Moreover, the speaker uses the first plural pronoun to indicate his position as the representative of the Iraqi people against this issue, whereas, he uses the second and third pronouns to address his rivals in the KRG. At the semantic level, on the other hand, the speaker uses the two modals ‘must’ and ‘will’ to denote necessity and certainty respectively. As far as the categorization of people is concerned, he classifies people into in-groups and out-groups, i.e., positively and negatively